Systemic implications of metallic foreign body syndrome in dairy cattle (Research, Society and Development, 2021)
This study aimed to evaluate the systemic implications of 37 cattle with traumatic reticulitis, evaluating clinical, laboratory, ultrasonographic and necroscopic changes. A clinical, laboratory and ultrasonographic examination was performed, and the animals were distributed in reticuloperitonitis (GI; n=21) and reticulopericarditis (GII; n=16) traumatic, based on necropsy findings. Blood samples were taken for haematological tests, serum total protein, albumin, globulin, gamma glutamyltransferase (GGT), aspartate aminotransferase (AST), glutamate dehydrogenase (GLDH), creatinine, urea, cortisol, creatine kinase (CK), creatine kinase-MB (CK-MB), cardiac troponin-I (cTn-I), plasma glucose and L-lactate. The abdominocentesis was productive in eight GI (n=8) and seven GII (n=7) animals, allowing the evaluation of physical, cytological and biochemical characteristics of the peritoneal fluid as a total protein, albumin, GLDH, AST, GGT, glucose and L-lactate. Changes in behavior, appetite, dehydration and temperature were observed, most expressive in GII. Hematology showed neutrophilic leukocytosis with regenerative left shift and hyperfibrinogenemia in both groups. Increased globulin, L-lactate concentration and serum GGT, GLDH, CK and CK-MB activity were observed, as well as significant elevation of cTnI (p=0.0190) in GII. In the peritoneal fluid exudate was observed in both groups and a higher concentration of L-lactate in relation to plasma. Ultrasound revealed retocular, cardiac, hepatic and splenic abnormalities. The anatomopathological lesions confirmed the ultrasound findings of both groups. The understanding of the syndrome helps in the diagnosis, as well as the adoption of preventive measures, minimizing the economic impact caused to the dairy cattle breeding.